ENGAGING STUDENTS AS CO-RESEARCHERS TO CONDUCT FOCUS GROUPS WITH OLDER PEOPLE. (11th November 2018) - Kydd, A B; Smith, S; King, L; Gentleman, M; Walsh, N; Head, K; Smart, F
Abstract: The study is a partnership of nursing students, academics and older people, designed to hear the stories of older people's good and poor care in the community and within care settings. We recruited 27 older people aged 60–92 living in the community and nursing homes and 14 undergraduate second year student nurses. The study had three phases: - half day training with students; day for all participants when students interviewed older people; half day involving academics and students in the collaborative thematic analysis of the data. Four themes emerged: Vulnerability; Therapeutic relationships; Expectations; Organisational Issues. The themes highlighted the feelings of powerlessness by the older people, which could be alleviated by a therapeutic relationship with staff and by human touch. If people understood what was happening they felt more secure. There was a degree of forgiveness amongst participants when organisational pressures proved unhelpful, but not the fault of the staff.